2022
DOI: 10.3390/genes13081321
|View full text |Cite
|
Sign up to set email alerts
|

Complex Physical Structure of Complete Mitochondrial Genome of Quercus acutissima (Fagaceae): A Significant Energy Plant

Abstract: Quercus acutissima Carruth. is a Chinese important energy plant with high ecological and economic values. While the species chloroplast genome has been reported, its mitochondrial genome (mitogenome) is still unexplored. Here, we assembled and annotated the Q. acutissima mitogenome, and we compared its characteristic differences with several closely related species. The Q. acutissima mitogenome’s main structure is branched with three distinguished contigs (linear molecule 1, circular molecule 2, and circular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…GC content is also one of the important indicators for species evaluation, and C. acerifolia mitogenome GC content was 46.91%, which is similar to the GC content of the mitogenomes of most angiosperms ( Q. acutissima , 45.72%; Dalbergia odorifera , 45.1%, Cucumis hystrix , 44.59%; Elymus sibiricus ; 44.47%) and higher than that of the clematis chloroplast genome (37.87–38.19%) ( Hong et al, 2021 ; Liu et al, 2022 ; Xia et al, 2022 ). The C. acerifolia mitogenome exhibits a multi-branched structure (linear molecule 1 and circular molecule 2), and the vast majority of published plant mitogenomes are presented as circular DNA molecules, and there are also conformational forms such as Y- and H-type linear, but mitochondrial DNA in its real state is often a mixture of different conformational forms ( Backert and Börner, 2000 ; Kitazaki and Kubo, 2010 ; Bonen, 2014 ; Christensen, 2019 ).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…GC content is also one of the important indicators for species evaluation, and C. acerifolia mitogenome GC content was 46.91%, which is similar to the GC content of the mitogenomes of most angiosperms ( Q. acutissima , 45.72%; Dalbergia odorifera , 45.1%, Cucumis hystrix , 44.59%; Elymus sibiricus ; 44.47%) and higher than that of the clematis chloroplast genome (37.87–38.19%) ( Hong et al, 2021 ; Liu et al, 2022 ; Xia et al, 2022 ). The C. acerifolia mitogenome exhibits a multi-branched structure (linear molecule 1 and circular molecule 2), and the vast majority of published plant mitogenomes are presented as circular DNA molecules, and there are also conformational forms such as Y- and H-type linear, but mitochondrial DNA in its real state is often a mixture of different conformational forms ( Backert and Börner, 2000 ; Kitazaki and Kubo, 2010 ; Bonen, 2014 ; Christensen, 2019 ).…”
Section: Discussionmentioning
confidence: 71%
“…Although plant mitogenomes are very large, they do not contain many coding genes, typically 50-60 (Kitazaki and Kubo, 2010). With 55 genes (35 PCGs) annotated in the C. acerifolia mitogenome, which is close to the number of genes annotated in Actinidia chinensis (Wang et al, 2019), Quercus acutissima (Liu et al, 2022), and Populus simonii (Bi et al, 2022). The sequences of the coding regions of angiosperms account for only 7-17% of the total genome, and the rest is occupied by intergenic regions (Kubo and Newton, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, we also identified that four genes, atp8 , ccmB , mttB and sdh4 , may have undergone positive selection in the evolution of gymnosperms in most species. These four genes are involved in the biosynthesis of ATP synthase, ubiquinol cytochrome c reductase, transport membrane protein and succinate dehydrogenase, respectively [ 5 , 7 ]. Based on previous studies, it is speculated that these four genes may have undergone positive selection under environmental stress to generate new functions to adapt to the new environment.…”
Section: Discussionmentioning
confidence: 99%
“… 2019 ; Liu et al. 2022 ). Although plant mitogenomes are often assembled and displayed as circular maps, they mostly exist as complex and dynamic collections of linear DNA interspersed with smaller circular and branched configurations (Oldenburg and Bendich et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Quercus acutissima mt genome is a branched structure comprising one linear and two circular formations (Liu et al. 2022 ), the Abelmoschus esculentus mt genome is composed of one linear and one circular structure (Li et al. 2022 ), and the Ipomoea batatas mt genome is arranged as four circular sections (Yang et al.…”
Section: Discussionmentioning
confidence: 99%